FACTORS PROMOTING SOCIAL MEDIA USE IN LOCAL GOVERNMENTS IN LATVIA - Lase, Kate; Sloka, Biruta (University of Zagreb, 2022)
Use of the social media in local governments has expanded around the world on the basis of development of internet and technology. Although each social network offers substantial benefits and opportunities, not all local governments use them or do not use them efficiently enough. Most local governments in Latvia use social media un do it for variety of reasons, but studies on the factors that promote the creation and maintenance of social network accounts in local governments in Latvia remains scant. The aim of the study is to analyse factors that promote social media use in local governments in Latvia and make proposals to policy makers. In order to achieve the purpose, the tasks are formulated as follows: 1. to review theoretical background of social media use in local governments; 2. to review existing research of social media use in local governments; 3. to analyse factors that can promote social media use in local governments in Latvia. Research methods used in preparation of the paper: recent scientific publication studies, analysis of social media of municipalities of Latvia, survey on social media use in municipalities in Latvia realized on April 2021. For data analysis there were used indicators of descriptive statistics: indicators of central tendency or location (arithmetic mean, mode, median, quartiles), indicators of variability (variance, standard deviation, standard error of mean), cross – tabulations. The results show that most local governments generally have positive views of their social media use but the real application of social media is not consistent in each local government. Majority of local governments in Latvia use at least two social media and one of them is Facebook. The results of the research can provide valuable pointers for decision makers how to improve social media use in local governments in Latvia. Thus, this study contributes to the debate on local government transparency and provides important guidelines for developing appropriate social media strategies and policies.
The research was supported by the NATIONAL RESEARCH PROGRAMME “LATVIAN HERITAGE AND FUTURE CHALLENGES FOR THE SUSTAINABILITY OF THE STATE” project “CHALLENGES FOR THE LATVIAN STATE AND SOCIETY AND THE SOLUTIONS IN INTERNATIONAL CONTEXT" (INTERFRAME-LV, Project No.VPP-IZM-2018/1-0005).
Keywords: Internet; local governments; regional development; social media; Research Subject Categories::SOCIAL SCIENCES::Business and economics